ANALISIS LITERASI NUMERASI DALAM MENYELESAIKAN SOAL ESSAY PADA PEMBELAJARAN BAHASA INDONESIA SDN BERANGAS BARAT 3 BARITO KUALA DESA BERANGAS BARAT KECAMATAN ALALAK KABUPATEN BARITO KUALA KALIMANTAN SELATAN - Tutus Rani Arifa; Sari Kumala; Jumiati; M. Iqbal Ansari; H. Abdul Hafiz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify and analyze students’ numeracy literacy skills in solving essay questions in Indonesian language learning at SDN Berangas Barat 3, Alalak District, Barito Kuala Regency. The research subjects consisted of 138 students from grades I–VI, along with classroom teachers as informants. The research employed a descriptive qualitative approach with a case study design. The instruments used included numerically-based essay questions, interview guidelines, and observation sheets. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques (Miles & Huberman). The findings revealed that some students still faced difficulties in connecting quantitative information with the context of Indonesian language texts, particularly in developing logical and structured essay responses. Factors influencing students’ numeracy literacy skills included limited understanding of numerical concepts, low reading interest, teachers’ instructional methods, and the availability of literacy resources at school. This study is expected to contribute to strengthening numeracy literacy in Indonesian language learning, particularly at the elementary school level.